Corticospinal tract alterations after ankle sprain in adolescence: Insights from the mouse model - Xiao'ao Xue; Xicheng Gu; Yuwen Zhang; Xuejun Wu; Tian Xia; Rong Lu; He Wang; Yinghui Hua (Sports Medicine and Health Science)
Purpose: Lateral ankle sprains (LAS) are associated with corticospinal pathway deficits. Existing evidence is primarily based on cross-sectional investigations and noncausal speculations. This study aims to determine whether maladaptive corticospinal pathway alterations occur pre- and postligament transection in LAS mouse models. Additionally, this study explores whether the alterations are more pronounced in adolescent mice than adults. Methods: Twenty-four 8-week-old adolescent and twenty-four 24-week-old adult mice were randomly assigned to lateral ankle ligament transection or sham surgery. Diffusion-weighted imaging of the corticospinal pathway was performed presurgery and 8 weeks postsurgery. Fractional anisotropy (FA) values, reflecting fiber integrity within the corticospinal subregions of the medulla, pons, midbrain, and cerebrum, were extracted. Results: Overall, 41 mice completed repeated image acquisition. Before surgery, no significant group effects on FA within the four corticospinal subregions were detected in either adolescent or adult mice. Two months after surgery, the adolescent cohort displayed a significant reduction in FA in the medulla subregion following ankle ligament transection (β-baseline-adjusted ​= ​−0.083, 95% CI, −0.145 to −0.021, p-corrected ​= ​0.048). Conversely, no significant effects of ankle ligament transection on corticospinal FA were observed in the adult cohort. Conclusion: The maladaptive alterations in the corticospinal tract could be observed in the adolescent LAS mouse model, characterized by reduced fiber integrity in the medulla subregion. While these results are derived from an animal model, they provide a foundation for future investigations into the mechanisms underlying neurological deficits following musculoskeletal injuries.